Home range size and foraging niche predict lead exposure variability in terrestrial birds - Max M Gillings; Riccardo Ton; Simon C Griffith (Ecotoxicology, 2026)

Historical bottlenecks and restricted gene flow in one of the last remaining stronghold populations of the southern black-throated finch (Poephila cincta cincta) - Skye Davis; Adam J. Stow; Jemma McCrossin; Wilbur Ashley; John M. van Osta; Brad Dreis; Simon C. Griffith (Conservation Genetics, 2026)
Habitat fragmentation is a key driver of reduced genetic connectivity and loss of genetic variation among populations, elevating the risk of inbreeding depression and reduced adaptive potential. The black-throated finch ( Poephila cincta ) is an endemic Australian finch with two recognised subspecies, a northern ( P. c. atropygialis ) and southern form ( P. c. cincta ) separated by a biogeographic barrier in northern Australia. The southern subspecies is nationally endangered and has experienced severe range contractions since the rise of pastoralism, with only two stronghold populations remaining (Townsville Coastal Plain and Desert Uplands Bioregion). Using a panel of more than 14,000 genome-wide single nucleotide polymorphisms for 107 individuals, we characterised spatial genetic structure for the Desert Uplands population. We mapped effective migration surfaces and tested for isolation by resistance to identify potential barriers to gene flow, estimated contemporary effective population sizes and reconstructed the demographic history of this population. We found evidence of restricted gene flow between localities only 16 km apart and strong isolation by geographic distance. Landscape resistance modelling identified areas of suitable woodland habitat that facilitated effective dispersal. More restricted gene flow in the southern range of this population is likely influenced by the fragmentation of suitable vegetation communities. Contemporary effective population sizes were near or below 1000, and we detected two historical population bottlenecks (> 50% decline) occurring around 60–100 and 700 years ago. Given recent evidence that the Desert Uplands population is genetically isolated from the only other stronghold population in Townsville, the results of this study suggest future losses of genetic diversity and adaptive potential may continue without effective management. To improve the long-term persistence of southern-black throated finch across their range, prioritising the conservation and restoration of habitat that promotes genetic connectivity is essential.

Assessing the vulnerability of elasmobranchs to western and central Pacific tuna fisheries using an improved ecological risk assessment method - Nicholas J. Hill; Shane Griffiths; Valerie Allain; Simon Nicol; Joanne Potts; Naiten Bradley Phillip; Cassandra L. Rigby (Fisheries Research, 2026)

Environmental uncertainty affects movement and space-use in sheep - Sarah T. Bartsch; William H. E. J. van Wettere; Simon C. Griffith; Stephan T. Leu (Behavioral Ecology and Sociobiology, 2026)
Animals regularly experience periods of food uncertainty due to seasonal changes and environmental variability. Further, the changing climate is leading to more variable weather patterns, which alter environmental conditions, and can result in resource distributions being less predictable in space and time. How animals respond to uncertain conditions, and in particular a changing distribution of food resources, remains largely unclear and is an important question in the field of movement and animal ecology. We used an experimental approach to study how Merino sheep ( Ovis aries ) respond to different levels of food location uncertainty in a drought-impacted region of the Australian arid zone. Sheep were unfamiliar with the experimental food locations at the start and progressively decreased their uncertainty (i.e., increased their environmental knowledge) when discovering an increasing number of foraging patches. We tracked 50 sheep with GPS collars (1 location every 15 s) and deduced their movement and space use behaviour. When food uncertainty decreased, individuals moved more directionally (greater step length, smaller turn angles) and moved greater distances per day. They also had larger daily ranges. Displacement (distance between first and last location of the day) increased once and otherwise remained similar across levels of uncertainty. Our study demonstrates how an arid zone ungulate, in a large 600 ha enclosed paddock, adjusted its movement and space use behaviour as it gained environmental information on food distribution. Our study provides important insights into how animals cope with variable environments in order to forage efficiently during periods of uncertainty. Significance statement Food distributions are often unpredictable over time, with climate change exacerbating variability. Understanding how animals respond to periods of environmental uncertainty is crucial to predict animal movement in space and time. We used an experimental approach and investigated how different levels of food location uncertainty affected the movement and space-use behaviour in sheep freely moving in a large 600 ha paddock. We used the number of discovered experimental food patches as a proxy for environmental knowledge (inverse of uncertainty). Movement was faster and more directional, and daily range size increased as food uncertainty decreased and sheep gained knowledge about the food locations. Our study demonstrates how an arid zone ungulate adjusted its movement and space use behaviour as it gained environmental information about food patch distributions.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Heterogeneity in seed traits: an overlooked breeding opportunity - Luqman B. Safdar; Ian D. Fisk; Rahul A. Bhosale; Simon Griffiths; Malcolm J. Hawkesford; Scott A. Boden; M. John Foulkes (Trends in Plant Science, 2026)

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

The thermal range of the wild zebra finch in developmental, reproductive, and phylogenetic contexts - Simon C. Griffith; Carmen R.B. da Silva; Riccardo Ton (Journal of Thermal Biology, 2025)

Spatial extent and age-related bioaccumulation of fluoride in the bones of house sparrows around aluminium smelting operations - Max M. Gillings; Riccardo Ton; Phoebe Lewis; Minna Saaristo; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2025)

Telomere length declines with mean blood lead concentration in an urban passerine - Heung Ying Janet Chik; Max M. Gillings; Riccardo Ton; Marco van der Velde; Mark Patrick Taylor; John P. Swaddle; Hannah L. Dugdale; Simon C. Griffith (Environmental Research, 2025)

Factors influencing species reintroduction success - Gemma Harding; Richard A. Griffiths; Simon A. Black (Biodiversity and Conservation, 2025)
Conservation reintroductions are widespread in species conservation but evaluation of their success, and particularly the reporting of failures is lacking. Here we evaluate aspects of species reintroduction that influence success and how conservation practitioners measure success. We analysed trends and reasons for perceived failure and success across 341 documented reintroduction case studies from across the globe. Reintroductions in Africa had lower scores for success compared to East Europe, North & Central Asia; fish had higher scores than invertebrates; and government and non-government organisations scored projects as more successful than did zoos or aquaria. Goals and Indicators do not appear to influence the success score, although too many goals may have a negative influence on success. Qualitative analysis of the reasons for failure and success showed that activities linked to Partnerships & Support (e.g. community support, government partnerships) were the most regularly cited reason for success, and Habitat & Release site (e.g. poor habitat connectivity, lack of suitable release sites) were the most frequently cited reason linked to failure, or failed elements. Current conservation efforts continue to comprise a disproportionately high number of reintroductions for mammals and birds compared to other taxa, and the number of reintroductions in developed countries outweigh those of developing countries.

Quantifying placebo and trial participation effects on cognitive outcome measures in aging dogs - Katherine E. Simon; Katharine Russell; Alejandra Mondino; Chin-Chieh Yang; Beth C. Case; Zachary Anderson; Christine Whitley; Emily Griffith; Margaret E. Gruen; Natasha J. Olby (GeroScience, 2025)
The placebo effect, or the positive effects observed after an inert treatment which result from patients’ expectations for the therapy, is well documented in human medicine. However, in veterinary medicine, where owner’s expectations serve as a proxy for their pets, it remains underexplored, particularly for elderly dogs with cognitive decline. To address this gap, we examined 21 dogs (mean age: 12.85 years, SD: 1.46) from a placebo group in a randomized controlled trial (RCT) and compared their results to 17 dogs (mean age: 13.24 years, SD:1.56) from an observational, longitudinal study to distinguish placebo effect from trial participation effect. Both populations had statistically comparable baseline data. Cognitive changes were evaluated with two remotely administered owner questionnaires (Canine Cognitive Dysfunction Scale (CCDR) and Canine Dementia Scale (CADES)) and three in-house cognitive assessments (Cylinder Task, Detour and Sustained Gaze). We hypothesized that placebo effect would be greater than trial participation effect, particularly in owner-reported measures. Matched pairs T -tests and effect size calculations (Hedge’s g ) were used to calculate changes across 6 months. A strong ( g = 0.76), significant ( p = 0.021) improvement in CADES was observed in the placebo cohort after 6 months, while no changes were detected with CCDR. Conversely, the observational cohort showed a small ( g = 0.35) and significant ( p = 0.03) deterioration on CCDR, and no change in CADES. No significant changes were noted on the in-house cognitive assessments in either cohort. We conclude that study context influences remotely delivered owner assessments and CCDR is more robust against caregiver placebo effect in RCTs than CADES.

Exposure to lead (Pb) contamination heightens predator avoidance behaviours in an urban bird - Heung Ying Janet Chik; Joseph F. Di Liberto; Max M. Gillings; Riccardo Ton; Mark Patrick Taylor; John P. Swaddle; Simon C. Griffith (Animal Behaviour, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Evaluating public exposure to airborne particulates from major incident fires: A back trajectory plume modelling approach - Simon D. Griffiths; Helen M. King; Justine Wilkinson; Frank J. Kelly; Jane A. Entwistle; Michael E. Deary (Journal of Hazardous Materials, 2025)

Animal social networks are robust to changing association definitions - Alex Hoi Hang Chan; Jamie Dunning; Kristina B Beck; Terry Burke; Heung Ying Janet Chik; Daniel Dunleavy; Tim Evans; André Ferreira; Babette Fourie; Simon C. Griffith; Friederike Hillemann; Julia Schroeder (Behavioral Ecology and Sociobiology, 2025)
The interconnecting links between individuals in an animal social network are often defined by discrete, directed behaviours, but where these are difficult to observe, a network link (edge) may instead be defined by individuals sharing a space at the same time, which can then be used to infer a social association. The method by which these associations are defined should be informed by the biological significance of edges, and therefore often vary between studies. Identifying an appropriate measure of association remains a challenge to behavioural ecologists. Here, we use automatically recorded feeder visit data from four bird systems to compare three methods to identify a social association: (1) strict time-window, (2) co-occurrence in a group, and (3) arrival-time. We tested the similarity of the resulting networks by comparing the repeatability and sensitivity of individuals’ social traits (network degree, strength, betweenness). We found that networks constructed using different methods but applying similar, ecologically relevant definitions of associations based on individuals’ spatio-temporal co-occurrence, showed similar characteristics. Our findings suggest that the different methods to construct animal social networks are comparable, but result in subtle differences driven by species biology and feeder design. We urge researchers to carefully evaluate the ecological context of their study systems when making methodological decisions. Specifically, researchers in ecology and evolution should carefully consider the biological relevance of an edge in animal social networks, and the implications of adopting different definitions.

Genetic analysis of grain protein content and deviation in wheat - Rohan Richard; Alison Lovegrove; Paola Tosi; Richard Casebow; Mervin Poole; Luzie U. Wingen; Simon Griffiths; Peter R. Shewry (Journal of Cereal Science, 2025)

Optimising the reintroduction of a specialist peatland butterfly Coenonympha tullia onto peatland restoration sites - Andrew Osborne; Sarah Griffiths; Simon Caporn; Emma Coulthard (Journal of Insect Conservation, 2024)
The two main goals of peatland restoration are habitat improvement and climate change mitigation by reducing greenhouse gas emissions from damaged peatlands and providing a net carbon sink. The biodiversity of specialist peatland species is threatened because of habitat destruction and the large heath butterfly Coenonympha tullia has become a flagship species for peatland ecosystem restoration, with a species reintroduction programme currently underway on a peatland restoration site within Chat Moss, Greater Manchester, UK. The aim of this study was to improve our quantitative understanding of C. tullia habitat resource requirements to optimise habitat restoration for further reintroduction attempts. We monitored butterfly micro-distribution and dispersal during the first three flight seasons (2020, 2021 and 2022) of the reintroduction using high-accuracy GPS, combined with a distance-bearing protocol. Analysis of butterfly flight points and rest points in relation to plant species distribution and abundance, identified the most important habitat resources. Using logistic regression, treatment-response curves were constructed, enabling us to identify critical thresholds for the abundance of these important habitat resources. The break of slope near the top of the logistic curve was identified using segmented regression, giving an estimate of the near-optimal abundance; fourteen Eriophorum vaginatum tussocks per 2 m quadrat and 13.4% Erica tetralix cover. Implications for insect conservation During ecosystem restorations, prior to the reintroduction of species with specialist habitat requirements, it is necessary to have a clear understanding of the abundance of the important habitat resources that need to be provided. The quantitative approach we describe defines the most significant environmental factors and habitat resources, then uses segmented regression to estimate the near-optimal habitat resource requirements; increasing the likelihood of reintroduced populations thriving and reintroduction programmes achieving long-term success.

Blood lead increases and haemoglobin decreases in urban birds along a soil contamination gradient in a mining city - Max M. Gillings; Riccardo Ton; Tiarne Harris; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Mitonuclear interactions impact aerobic metabolism in hybrids and may explain mitonuclear discordance in young, naturally hybridizing bird lineages - Callum S. McDiarmid; Daniel M. Hooper; Antoine Stier; Simon C. Griffith (Molecular Ecology, 2024)
Understanding genetic incompatibilities and genetic introgression between incipient species are major goals in evolutionary biology. Mitochondrial genes evolve rapidly and exist in dense gene networks with coevolved nuclear genes, suggesting that mitochondrial respiration may be particularly susceptible to disruption in hybrid organisms. Mitonuclear interactions have been demonstrated to contribute to hybrid dysfunction between deeply divergent taxa crossed in the laboratory, but there are few empirical examples of mitonuclear interactions between younger lineages that naturally hybridize. Here, we use controlled hybrid crosses and high‐resolution respirometry to provide the first experimental evidence in a bird that inter‐lineage mitonuclear interactions impact mitochondrial aerobic metabolism. Specifically, respiration capacity of the two mitodiscordant backcrosses (with mismatched mitonuclear combinations) differs from one another, although they do not differ significantly from the parental groups or mitoconcordant backcrosses as we would expect of mitonuclear disruptions. In the wild hybrid zone between these subspecies, the mitochondrial cline centre is shifted west of the nuclear cline centre, which is consistent with the direction of our experimental results. Our results therefore demonstrate asymmetric mitonuclear interactions that impact the capacity of cellular mitochondrial respiration and may help to explain the geographic discordance between mitochondrial and nuclear genomes observed in the wild.

Exposure to Sublethal Concentrations of Lead (Pb) Affects Ecologically Relevant Behaviors in House Sparrows (Passer domesticus) - Joseph F. Di Liberto; Simon C. Griffith; Cara J. Hall; Alexandra S. Mendelsohn; John P. Swaddle (Archives of Environmental Contamination and Toxicology, 2024)
Global contamination of environments with lead (Pb) poses threats to many ecosystems and populations. While exposure to Pb is toxic at high concentrations, recent literature has shown that lower concentrations can also cause sublethal, deleterious effects. However, there remains relatively little causal investigation of how exposure to lower concentrations of environmental Pb affects ecologically important behaviors. Behaviors often represent first-line responses of an organism and its internal physiological, molecular, and genetic responses to a changing environment. Hence, better understanding how behaviors are influenced by pollutants such as Pb generates crucial information on how species are coping with the effects of pollution more broadly. To better understand the effects of sublethal Pb on behavior, we chronically exposed adult wild-caught, captive house sparrows ( Passer domesticus ) to Pb-exposed drinking water and quantified a suite of behavioral outcomes: takeoff flight performance, activity in a novel environment, and in-hand struggling and breathing rate while being handled by an experimenter. Compared to controls (un-exposed drinking water), sparrows exposed to environmentally relevant concentrations of Pb exhibited decreases in takeoff flight performance and reduced movements in a novel environment following 9–10 weeks of exposure. We interpret this suite of results to be consistent with Pb influencing fundamental neuro-muscular abilities, making it more difficult for exposed birds to mount faster movements and activities. It is likely that suppression of takeoff flight and reduced movements would increase the predation risk of similar birds in the wild; hence, we also conclude that the effects we observed could influence fitness outcomes for individuals and populations altering ecological interactions within more naturalistic settings.

Concurrent measurements of nitrate at urban and suburban sites identify local nitrate formation as a driver for urban episodic PM2.5 pollution - Jinjian Li; Simon C.H. Ho; Stephen M. Griffith; Yeqi Huang; Rico K.Y. Cheung; Mattias Hallquist; Åsa M. Hallquist; Peter K.K. Louie; Jimmy C.H. Fung; Alexis K.H. Lau; Jian Zhen Yu (Science of The Total Environment, 2023)

Effects of heat waves on telomere dynamics and parental brooding effort in nestlings of the zebra finch ( Taeniopygia castanotis ) transitioning from ectothermy to endothermy - Riccardo Ton; Winnie Boner; Shirley Raveh; Pat Monaghan; Simon C. Griffith (Molecular Ecology, 2023)
Heat waves are predicted to be detrimental for organismal physiology with costs for survival that could be reflected in markers of biological state such as telomeres. Changes in early life telomere dynamics driven by thermal stress are of particular interest during the early post‐natal stages of altricial birds because nestlings quickly shift from being ectothermic to endothermic after hatching. Telomeres of ectothermic and endothermic organisms respond differently to environmental temperature, but few investigations within species that transition from ectothermy to endothermy are available. Also, ambient temperature influences parental brooding behaviour, which will alter the temperature experienced by offspring and thereby, potentially, their telomeres. We exposed zebra finch nestlings to experimental heat waves and compared their telomere dynamics to that of a control group at 5, 12 and 80 days of age that encapsulate the transition from the ectothermic to the endothermic thermoregulatory stage; we also recorded parental brooding, offspring sex, mass, growth rates, brood size and hatch order. Nestling mass showed an inverse relationship with telomere length, and nestlings exposed to heat waves showed lower telomere attrition during their first 12 days of life (ectothermic stage) compared to controls. Additionally, parents of heated broods reduced the time they spent brooding offspring (at 5 days old) compared to controls. Our results indicate that the effect of heat waves on telomere dynamics likely varies depending on age and thermoregulatory stage of the offspring in combination with parental brooding behaviour during growth.

Short- and long-term consequences of heat exposure on mitochondrial metabolism in zebra finches (Taeniopygia castanotis) - Hector Pacheco-Fuentes; Riccardo Ton; Simon C. Griffith (Oecologia, 2023)
Understanding the consequences of heat exposure on mitochondrial function is crucial as mitochondria lie at the core of metabolic processes, also affecting population dynamics. In adults, mitochondrial metabolism varies with temperature but can also depend on thermal conditions experienced during development. We exposed zebra finches to two alternative heat treatments during early development: “constant”, maintained birds at ambient 35 °C from parental pair formation to fledglings’ independence, while “periodic” heated broods at 40 °C, 6 h daily at nestling stage. Two years later, we acclimated birds from both experiments at 25 °C for 21 days, before exposing them to artificial heat (40 °C, 5 h daily for 10 days). After both conditions, we measured red blood cells’ mitochondrial metabolism using a high-resolution respirometer. We found significantly decreased mitochondrial metabolism for Routine, Oxidative Phosphorylation (OxPhos) and Electron Transport System maximum capacity (ETS) after the heat treatments. In addition, the birds exposed to “constant” heat in early life showed lower oxygen consumption at the Proton Leak (Leak) stage after the heat treatment as adults. Females showed higher mitochondrial respiration for Routine, ETS and Leak independent of the treatments, while this pattern was reversed for OxPhos coupling efficiency (OxCE). Our results show that short-term acclimation involved reduced mitochondrial respiration, and that the reaction of adult birds to heat depends on the intensity, pattern and duration of temperature conditions experienced at early-life stages. Our study provides insight into the complexity underlying variation in mitochondrial metabolism and raises questions on the adaptive value of long-lasting physiological adjustments triggered by the early-life thermal environment.

Associations between DNA methylation and telomere length during early life: Insight from wild zebra finches ( Taeniopygia guttata ) - Elizabeth L. Sheldon; Riccardo Ton; Winnie Boner; Pat Monaghan; Shirley Raveh; Aaron W. Schrey; Simon C. Griffith (Molecular Ecology, 2022)
Telomere length and DNA methylation (DNAm) are two promising biomarkers of biological age. Environmental factors and life history traits are known to affect variation in both these biomarkers, especially during early life, yet surprisingly little is known about their reciprocal association, especially in natural populations. Here, we explore how variation in DNAm, growth rate, and early‐life conditions are associated with telomere length changes during development. We tested these associations by collecting data from wild, nestling zebra finches in the Australian desert. We found that increases in the level of DNAm were negatively correlated with telomere length changes across early life. We also confirm previously documented effects of post hatch growth rate and clutch size on telomere length in a natural ecological context for a species that has been extensively studied in the laboratory. However, we did not detect any effect of ambient temperature during developmental on telomere length dynamics. We also found that the absolute telomere length of wild zebra finches, measured using the in‐gel TRF method, was similar to that of captive birds. Our findings highlight exciting new opportunities to link and disentangle potential relationships between DNA based biomarkers of ageing, and of physiological reactions to environmental change.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Sperm Sizer: a program to semi-automate the measurement of sperm length - Callum S. McDiarmid; Roger Li; Ariel F. Kahrl; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2021)

Communal roosting shows dynamics predicted by direct and indirect nepotism in chestnut-crowned babblers - Fumiaki Y. Nomano; James L. Savage; Lee A. Rollins; Simon C. Griffith; Andrew F. Russell (Behavioral Ecology and Sociobiology, 2021)

In-situ Image Analysis of Habitat Heterogeneity and Benthic Biodiversity in the Prince Gustav Channel, Eastern Antarctic Peninsula - Peter M. Almond; Katrin Linse; Simon Dreutter; Susie M. Grant; Huw J. Griffiths; Rowan J. Whittle; Melanie Mackenzie; William D. K. Reid (Frontiers in Marine Science, 2021)
Habitat heterogeneity is important for maintaining high levels of benthic biodiversity. The Prince Gustav Channel, on the Eastern Antarctic Peninsula, is characterized by an array of habitat types, ranging from flat, mud-dominated sheltered bays to steep and rocky exposed slopes. The channel has undergone dramatic environmental changes in recent decades, with the southern end of the channel permanently covered by the Prince Gustav Ice Shelf until it completely collapsed in 1995. Until now the marine benthic fauna of the Prince Gustav Channel has remained unstudied. A shallow underwater camera system and Agassiz trawl were deployed at different locations across the channel to collect information on habitat type and heterogeneity, benthic community composition and macrofaunal biomass. The texture of the seafloor was found to have a significant influence on the benthos, with hard substrates supporting higher abundances and diversity. Suspension and filter feeding organisms, including porifera, crinoids, and anthozoans, were strongly associated with hard substrates, with the same being true for deposit feeders, such as holothurians, and soft sediments. Habitat heterogeneity was high across the Prince Gustav Channel, particularly on a local scale, and this was significant in determining patterns of benthic composition and abundance. Other physical variables including depth and seafloor gradient played significant, interactive roles in determining composition potentially mediated through other processes. Sites that were once covered by the Prince Gustav Ice Shelf held distinct and unique communities, suggesting that the legacy of the ice shelf collapse may still be reflected in the benthos. Biomass estimations suggest that critical thresholds of vulnerable marine ecosystem indicator taxa, as defined by the Commission for the Conservation of Antarctic Marine Living Resources, have been met at multiple locations within the Prince Gustav Channel, which has implications for the future establishment of no take zones and marine protected areas within the region.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Reproductive coordination breeds success: the importance of the partnership in avian sperm biology - Laura L. Hurley; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Extra‐pair paternity in birds - Lyanne Brouwer; Simon C. Griffith (Molecular Ecology, 2019)
Since the first molecular study providing evidence for mating outside the pair bond in birds over 30 years ago, >500 studies have reported rates of extra‐pair paternity (EPP) in >300 bird species. Here, we give a detailed overview of the current literature reporting EPP in birds and highlight the sampling biases and patterns in the data set with respect to taxonomy, avian phylogeny and global regions, knowledge of which will be crucial for correct interpretation of results in future comparative studies. Subsequently, we use this comprehensive dataset to simultaneously test the role of several ecological and life history variables. We do not find clear evidence that variation in EPP across socially monogamous species can be explained by latitude, density (coloniality), migration, generation length, genetic structuring (dispersal distance), or climatic variability, after accounting for phylogeny. These results contrast previous studies, most likely due to the large heterogeneity within species in both EPP and the predictor of interest, indicating that using species averages might be unreliable. Despite the absence of broadscale ecological drivers in explaining interspecific variation in EPP, we suggest that certain behaviours and ecological variables might facilitate or constrain EPP, as indicated by our finding that EPP was negatively associated with latitude within noncolonial species, suggesting a role of breeding synchrony. Thus, rather than focussing on general explanations for variation in EPP across all species, a future focus should be on how various aspects of ecology or life history might have driven variation in EPP among groups of species or populations of the same species. Hence, we argue that variation in EPP can be partly explained when taking the right perspective. This comprehensive overview, and particularly the dataset provided herein will create a foundation for further studies.

Sex chromosome inversions enforce reproductive isolation across an avian hybrid zone - Daniel M. Hooper; Simon C. Griffith; Trevor D. Price (Molecular Ecology, 2019)
Across hybrid zones, the sex chromosomes are often more strongly differentiated than the autosomes. This is regularly attributed to the greater frequency of reproductive incompatibilities accumulating on sex chromosomes and their exposure in the heterogametic sex. Working within an avian hybrid zone, we explore the possibility that chromosome inversions differentially accumulate on the Z chromosome compared to the autosomes and thereby contribute to Z chromosome differentiation. We analyse the northern Australian hybrid zone between two subspecies of the long‐tailed finch ( Poephila acuticauda ), first described based on differences in bill colour, using reduced‐representation genomic sequencing for 293 individuals over a 1,530‐km transect. Autosomal differentiation between subspecies is minimal. In contrast, 75% of the Z chromosome is highly differentiated and shows a steep genomic cline, which is displaced 350 km to the west of the cline in bill colour. Differentiation is associated with two or more putative chromosomal inversions, each predominating in one subspecies. If inversions reduce recombination between hybrid incompatibilities, they are selectively favoured and should therefore accumulate in hybrid zones. We argue that this predisposes inversions to differentially accumulate on the Z chromosome. One genomic region affecting bill colour is on the Z, but the main candidates are on chromosome 8. This and the displacement of the bill colour and Z chromosome cline centres suggest that bill colour has not strongly contributed to inversion accumulation. Based on cline width, however, the Z chromosome and bill colour both contribute to reproductive isolation established between this pair of subspecies.

Just a FAD ? Ecosystem impacts of tuna purse‐seine fishing associated with fish aggregating devices in the western Pacific Warm Pool Province - Shane P. Griffiths; Valerie Allain; Simon D. Hoyle; Tim A. Lawson; Simon J. Nicol (Fisheries Oceanography, 2019)
The western and central Pacific Ocean supports the world's largest tuna fisheries. Since the 1990s, the purse‐seine fishery has increasingly fished in association with fish aggregating devices ( FAD s), which has increased catches of juvenile bigeye and yellowfin tunas and vulnerable bycatch species (e.g., sharks). This has raised concerns regarding the sustainability of these species’ populations and the supporting ecosystem, but may provide improved food security of Pacific Island nations through utilisation of FAD ‐associated byproduct species (e.g., wahoo). An ecosystem model of the western Pacific Warm Pool Province was used to explore the potential ecological impacts of varying FAD fishing effort (±50% or 100%) over 30 years. The ecosystem has undergone a significant change in structure since 1980 from heavy exploitation of top predators (e.g., tunas) and “fishing up the food web” of high‐trophic‐level non‐target species. The ecosystem appeared resistant to simulated fishing perturbations, with only modest changes ( FAD effort by at least 50% was predicted to increase the biomass of tuna species and sharks and return the ecosystem structure to a pre‐industrial‐fishing state within 10 years. Spatial disaggregation of the model and integration of economic information are recommended to better capture ecological and economic changes that may result from fishing and/or climate impacts and to develop appropriate management measures in response.

Signatures of genetic adaptation to extremely varied Australian environments in introduced European house sparrows - Samuel C. Andrew; Henrik Jensen; Ingerid J. Hagen; Sarah Lundregan; Simon C. Griffith (Molecular Ecology, 2018)
Due to its history of multiple introductions to novel environments worldwide, the house sparrow has been used as a model species to study local adaption in invasive avian species. New genomic resources such as a custom 200K SNP array and a house sparrow reference genome provide great prospects for studying rapid local adaptation in this invasive species. Here, we analyse high‐density genomewide genetic data collected across an extensive range of temperate, arid and tropical climates, in Australian populations that were introduced from Europe 150 years ago. We used two population differentiation ( PD ) and two ecological association ( EA ) methods to identify putative loci subject to selection across these varied climates. A majority of the outlier SNP s were identified through the use of the latent factor mixed models ( LFMM ) EA method, but the BayeScEnv EA method had the strongest overlap with the outliers from the two PD methods. Out of all the 971 outliers identified across the different methods, 38.3% were physically linked (within 20 kbps) to 575 known protein‐coding regions in the house sparrow reference genome. Interestingly, some outlier genes had been previously identified in genome scan studies of broadly distributed species or had strong links to traits that are expected to be important to local adaptation, for example, heat‐shock proteins, immune response and HOX genes. However, many outliers still have unknown relevance and some outliers can be false positives. Our results identify an opportunity to use the house sparrow model to further study local adaptation in an invasive species.

Wild zebra finches do not use social information from conspecific reproductive success for nest site choice and clutch size decisions - Hanja B. Brandl; Simon C. Griffith; Wiebke Schuett (Behavioral Ecology and Sociobiology, 2018)

Genetic diversity through time and space: diversity and demographic history from natural history specimens and serially sampled contemporary populations of the threatened Gouldian finch (Erythrura gouldiae) - Peri E. Bolton; Lee A. Rollins; James Brazill-Boast; Kimberley L. Maute; Sarah Legge; Jeremy J. Austin; Simon C. Griffith (Conservation Genetics, 2018)

The genetic structure of the introduced house sparrow populations in Australia and New Zealand is consistent with historical descriptions of multiple introductions to each country - Samuel C. Andrew; Monica Awasthy; Peri E. Bolton; Lee A. Rollins; Shinichi Nakagawa; Simon C. Griffith (Biological Invasions, 2018)

Practitioner and scientist perceptions of successful amphibian conservation - Helen M.R. Meredith; Freya A.V. St. John; Ben Collen; Simon A. Black; Richard A. Griffiths (Conservation Biology, 2018)
Conservation requires successful outcomes. However, success is perceived in many different ways depending on the desired outcome. Through a questionnaire survey, we examined perceptions of success among 355 scientists and practitioners working on amphibian conservation from over 150 organizations in more than 50 countries. We also sought to identify how different types of conservation actions and respondent experience and background influenced perceptions. Respondents identified 4 types of success: species and habitat improvements (84% of respondents); effective program management (36%); outreach initiatives such as education and public engagement (25%); and the application of science‐based conservation (15%). The most significant factor influencing overall perceived success was reducing threats. Capacity building was rated least important. Perceptions were influenced by experience, professional affiliation, involvement in conservation practice, and country of residence. More experienced practitioners associated success with improvements to species and habitats and less so with education and engagement initiatives. Although science‐based conservation was rated as important, this factor declined in importance as the number of programs a respondent participated in increased, particularly among those from less economically developed countries. The ultimate measure of conservation success—population recovery—may be difficult to measure in many amphibians; difficult to relate to the conservation actions intended to drive it; and difficult to achieve within conventional funding time frames. The relaunched Amphibian Conservation Action Plan provides a framework for capturing lower level processes and outcomes, identifying gaps, and measuring progress.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Association mapping of morphological traits in wild and captive zebra finches: reliable within, but not between populations - Ulrich Knief; Holger Schielzeth; Niclas Backström; Georg Hemmrich‐Stanisak; Michael Wittig; Andre Franke; Simon C. Griffith; Hans Ellegren; Bart Kempenaers; Wolfgang Forstmeier (Molecular Ecology, 2017)
Identifying causal genetic variants underlying heritable phenotypic variation is a long‐standing goal in evolutionary genetics. We previously identified several quantitative trait loci ( QTL ) for five morphological traits in a captive population of zebra finches ( Taeniopygia guttata ) by whole‐genome linkage mapping. We here follow up on these studies with the aim to narrow down on the quantitative trait variants ( QTN ) in one wild and three captive populations. First, we performed an association study using 672 single nucleotide polymorphisms ( SNP s) within candidate genes located in the previously identified QTL regions in a sample of 939 wild‐caught zebra finches. Then, we validated the most promising SNP –phenotype associations ( n = 25 SNP s) in 5228 birds from four populations. Genotype–phenotype associations were generally weak in the wild population, where linkage disequilibrium ( LD ) spans only short genomic distances. In contrast, in captive populations, where LD blocks are large, apparent SNP effects on morphological traits (i.e. associations) were highly repeatable with independent data from the same population. Most of those SNP s also showed significant associations with the same trait in other captive populations, but the direction and magnitude of these effects varied among populations. This suggests that the tested SNP s are not the causal QTN but rather physically linked to them, and that LD between SNP s and causal variants differs between populations due to founder effects. While the identification of QTN remains challenging in nonmodel organisms, we illustrate that it is indeed possible to confirm the location and magnitude of QTL in a population with stable linkage between markers and causal variants.

A Galaxy-based bioinformatics pipeline for optimised, streamlined microsatellite development from Illumina next-generation sequencing data - Sarah M. Griffiths; Graeme Fox; Peter J. Briggs; Ian J. Donaldson; Simon Hood; Pen Richardson; George W. Leaver; Nathan K. Truelove; Richard F. Preziosi (Conservation Genetics Resources, 2016)

Colour polymorphism is likely to be disadvantageous to some populations and species due to genetic architecture and morph interactions - Peri E. Bolton; Lee A. Rollins; Simon C. Griffith (Molecular Ecology, 2016)
Polymorphism describes two or more distinct, genetically determined, phenotypes that co‐occur in the same population, where the rarest morph is maintained at a frequency above the mutation rate (Ford 1945; Huxley 1955). In a recent opinion piece, we explored a new idea regarding the role of genetic architectures and morph interactions in colour polymorphisms and how this can negatively affect population performance (Bolton et al . 2015). In this issue of Molecular Ecology, Forsman (2016) thoroughly discusses the current evidence for polymorphisms enhancing population performance and critiques the validity of the definitions of polymorphism we use in our original paper. We respond by clarifying that the negative consequences of polymorphisms that we discussed are likely to be most pertinent in species that have a particular set of characteristics, such as strong sexual or social interactions between morphs and discrete genetic architectures. Although it was not our intention to redefine polymorphism, we do believe that there should be further discussion about refining or characterizing balanced polymorphisms with respect to the degree of morph sympatry, discreteness of traits and their underlying genetic architecture, and the types of selection that drive and maintain the variation. The latter describes whether polymorphism is primarily maintained by external factors such as predation pressure or internal factors such as interactions with members of the same species. The contribution of Forsman (2016) is useful to this discussion, and we hope that our exchange of opinions will inspire new empirical and theoretical ideas on the origin and maintenance of colour polymorphisms.

Back to the future: reflections and directions of South African marine bioinvasion research - ME Alexander; CA Simon; CL Griffiths; K Peters; S Sibanda; S Miza; B Groenewald; P Majiedt; KJ Sink; TB Robinson (African Journal of Marine Science, 2016)

Lost in translation? Standardising the terminology used in marine invasion biology and updating South African alien species lists - TB Robinson; ME Alexander; CA Simon; CL Griffiths; K Peters; S Sibanda; S Miza; B Groenewald; P Majiedt; KJ Sink (African Journal of Marine Science, 2016)

Sex steroid profiles and pair-maintenance behavior of captive wild-caught zebra finches (Taeniopygia guttata) - Nora H. Prior; Kang Nian Yap; Hans H. Adomat; Mark C. Mainwaring; H. Bobby Fokidis; Emma S. Guns; Katherine L. Buchanan; Simon C. Griffith; Kiran K. Soma (Journal of Comparative Physiology A, 2016)

Four-way development of microsatellite markers for the Gouldian finch (Erythrura gouldiae) - Kang-Wook Kim; Hanyuan Zhang; Gavin J. Horsburgh; Susannah Bird; Deborah A. Dawson; Simon C. Griffith; Terry Burke (Conservation Genetics Resources, 2015)

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Sequential polyandry through divorce and re-pairing in a cooperatively breeding bird reduces helper-offspring relatedness - Miyako H. Warrington; Lee Ann Rollins; Andrew F. Russell; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2015)

The danger within: the role of genetic, behavioural and ecological factors in population persistence of colour polymorphic species - Peri E. Bolton; Lee A. Rollins; Simon C. Griffith (Molecular Ecology, 2015)
Polymorphic species have been the focus of important work in evolutionary biology. It has been suggested that colour polymorphic species have specific evolutionary and population dynamics that enable them to persist through environmental changes better than less variable species. We suggest that recent empirical and theoretical work indicates that polymorphic species may be more vulnerable to extinction than previously thought. This vulnerability arises because these species often have a number of correlated sexual, behavioural, life history and ecological traits, which can have a simple genetic underpinning. When exacerbated by environmental change, these alternate strategies can lead to conflict between morphs at the genomic and population levels, which can directly or indirectly affect population and evolutionary dynamics. In this perspective, we identify a number of ways in which the nature of the correlated traits, their underpinning genetic architecture, and the inevitable interactions between colour morphs can result in a reduction in population fitness. The principles illustrated here apply to all kinds of discrete polymorphism (e.g. behavioural syndromes), but we focus primarily on colour polymorphism because they are well studied. We urge further empirical investigation of the genetic architecture and interactions in polymorphic species to elucidate the impact on population fitness.

Vegetation exerts a greater control on litter decomposition than climate warming in peatlands - Susan E. Ward; Kate H. Orwin; Nicholas J. Ostle; Maria J. I. Briones; Bruce C. Thomson; Robert I. Griffiths; Simon Oakley; Helen Quirk; Richard D. Bardgett (Ecology, 2015)
Historically, slow decomposition rates have resulted in the accumulation of large amounts of carbon in northern peatlands. Both climate warming and vegetation change can alter rates of decomposition, and hence affect rates of atmospheric CO 2 exchange, with consequences for climate change feedbacks. Although warming and vegetation change are happening concurrently, little is known about their relative and interactive effects on decomposition processes. To test the effects of warming and vegetation change on decomposition rates, we placed litter of three dominant species ( Calluna vulgaris , Eriophorum vaginatum , Hypnum jutlandicum ) into a peatland field experiment that combined warming with plant functional group removals, and measured mass loss over two years. To identify potential mechanisms behind effects, we also measured nutrient cycling and soil biota. We found that plant functional group removals exerted a stronger control over short‐term litter decomposition than did ~1°C warming, and that the plant removal effect depended on litter species identity. Specifically, rates of litter decomposition were faster when shrubs were removed from the plant community, and these effects were strongest for graminoid and bryophyte litter. Plant functional group removals also had strong effects on soil biota and nutrient cycling associated with decomposition, whereby shrub removal had cascading effects on soil fungal community composition, increased enchytraeid abundance, and increased rates of N mineralization. Our findings demonstrate that, in addition to litter quality, changes in vegetation composition play a significant role in regulating short‐term litter decomposition and belowground communities in peatland, and that these impacts can be greater than moderate warming effects. Our findings, albeit from a relatively short‐term study, highlight the need to consider both vegetation change and its impacts below ground alongside climatic effects when predicting future decomposition rates and carbon storage in peatlands.

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Establishing the A. E. Watkins landrace cultivar collection as a resource for systematic gene discovery in bread wheat - Luzie U. Wingen; Simon Orford; Richard Goram; Michelle Leverington-Waite; Lorelei Bilham; Theofania S. Patsiou; Mike Ambrose; Jo Dicks; Simon Griffiths (Theoretical and Applied Genetics, 2014)

Validation of an automated data collection method for quantifying social networks in collective behaviours - Fumiaki Y. Nomano; Lucy E. Browning; Shinichi Nakagawa; Simon C. Griffith; Andrew F. Russell (Behavioral Ecology and Sociobiology, 2014)

Morph-dependent resource acquisition and fitness in a polymorphic bird - James Brazill-Boast; Simon C. Griffith; Sarah R. Pryke (Evolutionary Ecology, 2013)

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Simon J. Nicol; Valerie Allain; Graham M. Pilling; Jeff Polovina; Marta Coll; Johann Bell; Paul Dalzell; Peter Sharples; Robert Olson; Shane Griffiths; Jeffrey M. Dambacher; Jock Young; et al. (Climatic Change, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Crops that feed the world 9. Oats- a cereal crop for human and livestock feed with industrial applications - Athole Marshall; Sandy Cowan; Simon Edwards; Irene Griffiths; Catherine Howarth; Tim Langdon; Ethel White (Food Security, 2013)

Does coloniality improve foraging efficiency and nestling provisioning? A field experiment in the wild Zebra Finch - Mylene M. Mariette; Simon C. Griffith (Ecology, 2013)
The foraging benefits of coloniality, whereby colony members exchange information about food location, have been suggested as a primary factor influencing the evolution of coloniality. However, despite its longstanding popularity, this hypothesis has rarely been tested experimentally. Here, we conducted a field experiment in the wild Zebra Finch Taeniopygia guttata to test whether colonial birds are better at finding food than solitary individuals. We manipulated food patch location and directly measured foraging activity of many colonial and solitary parents at those patches using an electronic monitoring system. We provided nesting sites in excess to alleviate nest site competition and manipulated brood size to eliminate the possible correlation between brood size, nesting density, and individual quality (including foraging activity). We found that solitary birds found experimental food patches first, closely followed by colonial birds. Moreover, solitary parents adjusted the amount of food per nestling to experimental brood size, whereas colonial parents did not, although overall, nestlings were fed more per capita in colonial than in solitary nests. In addition, brood size and, to a lesser extent, nesting density negatively affected nestling growth. Therefore, with the effect of provisioning rate, sibling competition, and cost of coloniality combined, nestling mass was not affected by the brood manipulation in solitary nests, whereas nestlings were lighter in enlarged than in reduced broods in colonies. Our results therefore suggest that individuals settling in solitary nests were intrinsically better foragers and more optimal parents. While they do not invalidate the possibility of information transfer at colonies, our findings highlight the importance of considering settlement bias in future studies and add to the existing evidence that the effects of nesting density on fitness are both complex and multiple.

Maternal effects on begging behaviour: an experimental demonstration of the effects of laying sequence, hatch order, nestling sex and brood size - Amanda J. Gilby; Enrico Sorato; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2012)

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Building genetic networks using relatedness information: a novel approach for the estimation of dispersal and characterization of group structure in social animals - LEE ANN ROLLINS; LUCY E. BROWNING; CLARE E. HOLLELEY; JAMES L. SAVAGE; ANDREW F. RUSSELL; SIMON C. GRIFFITH (Molecular Ecology, 2012)
Natal dispersal is an important life history trait driving variation in individual fitness, and therefore, a proper understanding of the factors underlying dispersal behaviour is critical to many fields including population dynamics, behavioural ecology and conservation biology. However, individual dispersal patterns remain difficult to quantify despite many years of research using direct and indirect methods. Here, we quantify dispersal in a single intensively studied population of the cooperatively breeding chestnut‐crowned babbler ( Pomatostomus ruficeps ) using genetic networks created from the combination of pairwise relatedness data and social networking methods and compare this to dispersal estimates from re‐sighting data. This novel approach not only identifies movements between social groups within our study sites but also provides an estimation of immigration rates of individuals originating outside the study site. Both genetic and re‐sighting data indicated that dispersal was strongly female biased, but the magnitude of dispersal estimates was much greater using genetic data. This suggests that many previous studies relying on mark–recapture data may have significantly underestimated dispersal. An analysis of spatial genetic structure within the sampled population also supports the idea that females are more dispersive, with females having no structure beyond the bounds of their own social group, while male genetic structure expands for 750 m from their social group. Although the genetic network approach we have used is an excellent tool for visualizing the social and genetic microstructure of social animals and identifying dispersers, our results also indicate the importance of applying them in parallel with behavioural and life history data.

International workshop on opportunities for ecosystem approaches to fisheries management in the Pacific Ocean tuna fisheries - Valerie Allain; Simon Nicol; Jeffrey Polovina; Marta Coll; Robert Olson; Shane Griffiths; Jeffrey Dambacher; Jock Young; Jesus Jurado Molina; Simon Hoyle; Tim Lawson (Reviews in Fish Biology and Fisheries, 2012)

Ecological effects of longline fishing and climate change on the pelagic ecosystem off eastern Australia - Shane P. Griffiths; Jock W. Young; Matt J. Lansdell; Robert A. Campbell; John Hampton; Simon D. Hoyle; Adam Langley; Donald Bromhead; Michael G. Hinton (Reviews in Fish Biology and Fisheries, 2010)

Meta-QTL analysis of the genetic control of ear emergence in elite European winter wheat germplasm - Simon Griffiths; James Simmonds; Michelle Leverington; Yingkun Wang; Lesley Fish; Liz Sayers; Leodie Alibert; Simon Orford; Luzie Wingen; Laurence Herry; Sebastien Faure; David Laurie; et al. (Theoretical and Applied Genetics, 2009)

Seasonal decline in reproductive performance varies with colony size in the fairy martin, Petrochelidon ariel - Michael J. L. Magrath; Peter Santema; Karen M. Bouwman; Dušan M. Brinkhuizen; Simon C. Griffith; Naomi E. Langmore (Behavioral Ecology and Sociobiology, 2009)

Neutrophils and TRAIL: insights into BCG immunotherapy for bladder cancer - Mark P. Simons; William M. Nauseef; Thomas S. Griffith (Immunologic Research, 2007)

A Pseudo-Response Regulator is misexpressed in the photoperiod insensitive Ppd-D1a mutant of wheat (Triticum aestivum L.) - James Beales; Adrian Turner; Simon Griffiths; John W. Snape; David A. Laurie (Theoretical and Applied Genetics, 2007)

Impaired hatching success and male-biased embryo mortality in Tree Sparrows - Magnus Svensson; Pekka T. Rintamäki; Tim R. Birkhead; Simon C. Griffith; Arne Lundberg (Journal of Ornithology, 2007)

A BIOPSY POLE SYSTEM FOR BOW‐RIDING DOLPHINS: SAMPLING SUCCESS, BEHAVIORAL RESPONSES, AND TEST FOR SAMPLING BIAS - Kerstin Bilgmann; Owen J. Griffiths; Simon J. Allen; Luciana M. Möller (Marine Mammal Science, 2007)

Construction and analysis of a BAC library in the grass Brachypodium sylvaticum : its use as a tool to bridge the gap between rice and wheat in elucidating gene content - Simon Griffiths; Sebastien Allouis; Graham Moore; Tracie N. Foote (Functional & Integrative Genomics, 2004)

Condition‐dependent sex allocation in a lek‐breeding wader, the ruff ( Philomachus pugnax ) - Katherine A. Thuman; Fredrik Widemo; Simon C. Griffith (Molecular Ecology, 2003)
Sex allocation theory predicts that females should bias the production of offspring towards the sex that will maximize maternal fitness. Here we demonstrate evidence for nonrandom sex allocation by female ruffs ( Philomachus pugnax ), at both the individual and population level in relation to female condition. At the population level, female condition varies significantly across 3 years and is mirrored by population sex ratio, such that in years when females are in poor condition the population offspring sex ratio is female‐biased, while in years when females are in better condition there was little or no bias. In the year when females were in overall poor condition, females in better condition produced more daughters. The same relationship is also revealed by comparing the sex ratios of individual females breeding in two consecutive years in different condition. As the condition of an individual female improves (across years) she tends to produce more female offspring. Although we have shown that, as in other birds, female condition is an important determinant of sex allocation, our results also suggest that such nonrandom allocation does not occur in every year, being particularly strong in a year when females, on average, are in poorer condition. We suggest that our results are consistent with the idea that skewing the sex ratio is likely to carry a cost to females and that it is adaptive only when the fitness differential between sons and daughters is sufficient to outweigh probable costs.

Extra pair paternity in birds: a review of interspecific variation and adaptive function - Simon C. Griffith; Ian P. F. Owens; Katherine A. Thuman (Molecular Ecology, 2002)
The application of molecular genetic techniques has revolutionized our view of avian mating systems. Contrary to prior expectations, birds are only very rarely sexually monogamous, with ‘extra‐pair offspring’ found in approximately 90% of species. Even among socially monogamous species, over 11% of offspring are, on average, the result of extra‐pair paternity (EPP). Based on over 150 molecular genetic studies of EPP in birds, we review two topical areas: (i) ecological explanations for interspecific variation in the rate of EPP; and (ii) evidence bearing on the adaptive function of EPP. We highlight the remaining challenges of understanding the relative roles of genes and ecology in determining variation between taxa in the rate of extra paternity, and testing for differences between extra‐pair offspring and those sired within‐pair.

Identification and Characterization of Segments 3 and 4 of the ISAV Genome - Rachael J. Ritchie; Joël Heppell; Marcia B. Cook; Simon Jones; Steve G. Griffiths (Virus Genes, 2001)